Bombs Away: Visual thinking and students’ engagement in design studios contexts - Chamorro-Koc, Marianella; Scott, Andrew; Coombs, Gretchen (Design and Technology Education: An International Journal, 2015)
In design studio, sketching or visual thinking is part of processes that assist students to achieve final design solutions. At QUT’s First and Third Year industrial design studio classes we engage in a variety of teaching pedagogies from which we identify ‘Concept Bombs’ as instrumental in the development of students’ visual thinking and reflective design process, and also as a vehicle to foster positive student engagement. In First year studios our Concept Bombs’ consist of 20 minute individual design tasks focusing on rapid development of initial concept designs and free-hand sketching. In Third Year studios we adopt a variety of formats and different timing, combining individual and team based tasks. Our experience and surveys tell us that students value intensive studio activities especially when combined with timely assessment and feedback. While conventional longer-duration design projects are essential for allowing students to engage with the full depth and complexity of the design process, short and intensive design activities introduce variety to the learning experience and enhance student engagement. This paper presents a comparative analysis of First and Third Year students’ Concept Bomb sketches to describe the types of design knowledge embedded in them, a discussion of limitations and opportunities of this pedagogical technique, as well as considerations for future development of studio based tasks of this kind as design pedagogies in the midst of current university education trends.